Exploring the Interplay Between Glycated Albumin, AGEs, and Inflammation in Old Patients with CKD - Simone Vettoretti; Lara Caldiroli; Paolo Molinari; Amanda Villa; Massimiliano M. Corsi Romanelli; Elena Vianello; Elena Dozio; Simonetta Genovesi (Metabolites, 2025)
Introduction: Chronic kidney disease (CKD) increases cardiovascular risk through mechanisms such as oxidative stress and the accumulation of advanced glycation end products (AGEs). Glycated albumin (GA) is associated with cardiovascular risk in CKD patients, but its relationship with AGEs and systemic inflammation remains unclear. This study investigated these associations in old patients with severe CKD, with and without diabetes. Methods: We conducted a cross-sectional analysis in 122 patients aged ≥ 65 years with CKD stages G3a–G5, including 67 diabetics and 55 non-diabetics. Patients with confounding comorbidities were excluded. We measured GA, AGEs, various AGEs receptors (RAGE) isoforms, and inflammatory cytokines (CRP, IL-6, TNFα, and MCP-1) using standardized assays. Statistical analyses included group comparisons, correlation coefficients, and multivariate regression. Results: Of 122 patients (mean age 77.7 ± 11.3 years), diabetics had higher GA percentages than non-diabetics (22.0 ± 7.1% vs. 17.5 ± 5.4%, p = 0.0001), while AGEs (2931 ± 763 vs. 3156 ± 809 AU; p = 0.118) and inflammatory markers (CRP 0.240[0.380] vs. 0.200[0.280] mg/dL; p = 0.142; IL-6 3.4[4.0] vs. 3.0[3.8] pg/mL; p = 0.238) were similar between groups. Overall, GA was inversely correlated with estimated glomerular filtration rate (eGFR) (ρ = −0.189, p = 0.037) and positively with glycated hemoglobin (HbA1c) (ρ = 0.525, p < 0.0001), but showed no significant correlation with AGEs, RAGE isoforms, or inflammatory cytokines. In multivariate analysis, only HbA1c remained independently associated with GA (β = 0.222, p = 0.005). Conclusions: In old patients with severe CKD, GA appears to be a more useful marker of glycemic control than glycation stress, the latter of which is the result of multiple factors, including impaired kidney function and systemic inflammation.